Determinación de costos por orden de producción en la microempresa “Creaciones Wiflo”, periodo del 01 de octubre al 31 de diciembre del 2021. - Tene Vera, Carolina Patricia (2022)
The Determination of Costs by production orders in the Creations Wiflo Microenterprise has been carried out with the following objectives: To make an inventory of all the goods owned by the Creations Wiflo microenterprise; Design the documents and auxiliary records for the control of the elements of the cost of production; Determine the costs by order of production of the products produced by the company Creations Wiflo; Make the statement of production costs and the production cost report, to know in a summarized and orderly way each of the values in relation to the element incurred in the preparation of each production order. In the present work, the determination of costs by production order was carried out, which began with the preparation of the initial inventory, the chart of accounts, the manual of accounts, the registration of the transactions of the daily book, the accounting majorization of the accounts, the trial balance, the work sheet and the realization of financial statements, as auxiliary documents of the production activity there is the realization of the production order, the Kardex cards and the requisition orders for the control of materials used, cards time and clock for the control of labor and the realization of the budget of indirect manufacturing costs, the same ones that are necessary for the elaboration of the cost sheets of each production order of the backpacks and briefcases in the microenterprise, and to its time to know the current situation of the company through the posting of the accounts, for the realization of the financial statements and the report end of costs incurred in the period. This determination process served for the microenterprise to have knowledge of the costs incurred during the execution of each production order, so that they can establish the profit margin that most benefits the company and in turn based on the documents designed at work can be used to make records of the elements used during the production process, to improve operational control in the institution.